Concentrating on zoo and wildlife species. (3rd September 2016) - Hydeskov, Helle; Jayson, Stephanie
Abstract : Helle Hydeskov and Stephanie Jayson are European College of Zoological Medicine residents on new three‐year training programmes being run jointly by the Zoological Society of London and the Royal Veterinary College. Here, they explain what motivated them to take up their residencies